2020
DOI: 10.1155/2020/6371201
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Activity of Aloe vera Leaves

Abstract: This research evaluated the potential of using the methanol extract of Aloe vera (L.) Burm.f (AVM) to prevent the formation of AGEs by means of the BSA/glucose assay, BSA-methylglyoxal assay, arginine-methylglyoxal assay, fructosamine, Nɛ-(carboxymethyl) lysine (CML), thiol groups, and carbonyl protein in vitro. The effect of AVM was also evaluated with regard to inhibiting the enzymes α-amylase, α-glucosidase, and pancreatic lipase. For this, the plant was dried, ground, and subsequently macerated with methan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 27 publications
0
15
0
5
Order By: Relevance
“…In 2020, Muñiz-Ramirez et al, reported the methanol leaves extract of A. vera (5 mg/mL) showed 87% inhibitory activity in α-amylase enzyme, while 66% was observed in α-glucosidase enzyme [ 282 ]. A. vera gel (200 and 300 mg/kg) alcoholic extracts on streptozotocin-induced diabetic rats have demonstrated that they can reduce blood glucose levels without harming the subject [ 283 ].…”
Section: Phytochemical and Experimental Studies Of Antidiabetic Plants In Bangladeshmentioning
confidence: 99%
“…In 2020, Muñiz-Ramirez et al, reported the methanol leaves extract of A. vera (5 mg/mL) showed 87% inhibitory activity in α-amylase enzyme, while 66% was observed in α-glucosidase enzyme [ 282 ]. A. vera gel (200 and 300 mg/kg) alcoholic extracts on streptozotocin-induced diabetic rats have demonstrated that they can reduce blood glucose levels without harming the subject [ 283 ].…”
Section: Phytochemical and Experimental Studies Of Antidiabetic Plants In Bangladeshmentioning
confidence: 99%
“…Hal yang serupa juga dilakukan oleh Ramirez (2020), mengevaluasi potensi penggunaan ekstrak metanol Aloe vera (L.) Burm (AVM) untuk mencegah AGEs melalui uji BSA/ glukosa, uji BSA-metilglioksal, uji arginin-metilglioksal, fruktosamin, Nε-(karboksimetil) lisin (CML), gugus tiol, dan protein karbonil secara in vitro. Efek positif dari AVM juga dievaluasi sehubungan dengan penghambatan enzim α-amilase, α-glukosidase, dan lipase pankreas.…”
Section: Hasil Dan Pembahasanunclassified
“…Selama berabad-abad, obat-obatan herbal telah banyak digunakan untuk mengobati berbagai macam penyakit. Sampai saat ini, banyak dari tanaman ini masih digunakan sebagai alternatif pertama untuk menyembuhkan penyakit tertentu di negara berkembang di seluruh dunia karena efek sampingnya yang sedikit, juga dilaporkan bahwa sekitar 20% obat yang digunakan di seluruh dunia berasal dari tumbuhan (Muñiz-Ramirez et al, 2020). Sehingga semakin berkembang minat untuk menemukan sumber tanaman yang aman dan tidak beracun untuk mencari obat alternatif atau pelengkap yang membantu pengobatan berbagai penyakit kronis seperti diabetes melitus.…”
unclassified
“…Aloe vera (Aloe barbadensis) (Ngo et al, 2010) Genus Aloe tumbuh di daerah kering, tropis, dan subtropis, yang genus ini mencakup sekitar 450 spesies. Aloe vera merupakan tanaman sukulen tanpa batang atau batang pendek dan dapat tumbuh setinggi 60−100 cm (Muñiz-Ramirez et al, 2020). Setiap tanaman aloe vera biasanya memiliki rata-rata 12-16 daun.…”
unclassified
See 1 more Smart Citation